Penerapan Model Pembelajaran Problem Based Learning untuk Meningkatkan Hasil Belajar Geografi Siswa Kelas X IPS SMA Negeri 11 Bombana Pada Materi Pokok Dinamika Atmosfer - Asyri Nursyahbana; Sitti Kasmiati; La Ode Nursalam; Syarifah (Jurusan Pendidikan Geografi FKIP Universitas Halu Oleo, 2023)
Low learning outcomes are often associated with the use of teaching methods that are inappropriate and still teacher-centred. This research aims to: 1) determine the significant differences between the average post-test and pre-test scores of experimental class and control class students; and 2) find out whether the average post-test score of experimental class students is significantly better than the post-test average of control class students in Class The type of research used is an experiment with a pre-test post-test control group design. The research results showed: 1) the average score for the experimental class learning outcomes was 41.10 for the pre-test and the post-test score was 84.66; and 2) the average value of the control class learning outcomes obtained by the pre-test was 40.15 and the post-test was 68.75, so the t-test results showed that the t value = 0.42 < 2.012 which means there is no significant difference with a significance level of 0.05%, and there is a significant difference in the average value of the post-test results for the experimental class and the control class with a value of t= 3.087> 2.012.